2016
DOI: 10.1039/c6ta03146c
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasoft gelatin aerogels for oil contaminant removal

Abstract: We demonstrated the preparation of a novel aerogel simply by crosslinking a gelatin physical gel with formaldehyde (cGel) and using a subsequent freeze-drying procedure. A hydrophobic absorbent material (MTCS-cGel aerogel) was further obtained by thermal chemical vapor deposition (CVD) of methyltrichlorosilane (MTCS).Rheological tests were carried out to investigate the cross-linking between gelatin and formaldehyde. Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energydis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 50 publications
0
45
0
1
Order By: Relevance
“…Considering the natural abundance, renewability, environmental friendliness, and low cost, biomass has been regarded as a renewable and sustainable carbon precursor for fabricating carbon aerogels. Up to now, several biomass‐derived carbon aerogels have been successfully developed from gelatin,16 winter melon,17 protein,18 bacterial cellulose,19 and raw cotton 20. However, those carbon aerogels show poor compressibility, elasticity, and fatigue resistance owing to the intrinsic random porous architecture and severe volume shrinkage at annealing or carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the natural abundance, renewability, environmental friendliness, and low cost, biomass has been regarded as a renewable and sustainable carbon precursor for fabricating carbon aerogels. Up to now, several biomass‐derived carbon aerogels have been successfully developed from gelatin,16 winter melon,17 protein,18 bacterial cellulose,19 and raw cotton 20. However, those carbon aerogels show poor compressibility, elasticity, and fatigue resistance owing to the intrinsic random porous architecture and severe volume shrinkage at annealing or carbonization.…”
Section: Introductionmentioning
confidence: 99%
“…It concludes that the storage modulus responses are more elastic at high frequency. [ 37 ] The difference in storage modulus is visualized due to the base catalyst (urea content) and precursor (MTMS) quantity variation in different specimens. After 24‐h aging at 70°C, the difference in the storage modulus pattern was M 10 U 2 > M 8 U 2 > M 6 U 2 , as shown in Figure 1(B).…”
Section: Resultsmentioning
confidence: 99%
“…48 In our case, there are two options for crosslinking. On the one hand, gelatin can be crosslinked in the presence of formaldehyde, 23 and NaCMC by adding N,N 0 -methylenebisacrylamide. 49 Our results have shown that water-insoluble swollen aerogels can be produced in the presence of bisacrylamide.…”
Section: Crosslinked Aerogelsmentioning
confidence: 99%
“…Both features are important for different applications such as spilled oil sorption and separation processes. 12,23 Therefore, a hierarchical porous structure with mesoporous and macroporous compartments is needed, which cannot be obtained by a classical freeze-drying process of a hydrogel. Emulsion-based porous systems are of interest in this context.…”
Section: Introductionmentioning
confidence: 99%